Kinship resources for the elderly. - Wachter, K W (1997)
As population ageing strains social insurance systems, cohorts whose own fertility was low will be reaching elderly status, leaving close biological kin in short supply. However, there is a countervailing trend, inasmuch as burgeoning divorce, remarriage and family blending have expanded the numbers and varieties of step-kin and other non-standard kinship ties. Methods of computer microsimulation in conjunction with richer sample surveys can help us to foresee the contours of kin numbers and kinship relations in the future. Prime areas include the likely frequency of kin-deprived elderly, the overlap with economic deprivation and the interaction between kin frequency and intensity of contact. Step-ties may be weaker but nonetheless critical in raising the probability of at least one compatible member with whom one can choose to maintain contact and rely on. Kinship networks extended through half- and step-links, by stretching across racial and economic lines, may promote social cohesion.